Avaliação da técnica de eletrodiálise para a separação de ácido lactobiônico produzido por via biotecnológica - Peretti, Fabíola Andreola (My University, 2014)
Glicose-fructose oxidoreductase (GFOR) and glicono-d-lactonase (GL) enzymes are present in Zymomonas mobilis bacteria cells. These enzymes are capable to catalyze lactobionic acid (AL) formation (or formation of its correspondent salts) together with sorbitol from lactose and fructose. Lactobionic acid and sodium lactobionate have important applications in medical area and cosmetic industry. GFOR and GL enzymes present higher activity at pH 6.4, thus being necessary correction of pH medium during AL formation process, in order to maintain pH around 6.4. Lactobionic acid separation using electrodialysis is possible since this acid is the only ionic component in bioconversion. Extraction of AL simultaneously to its formation could be advantageous since addition of alkali to the reaction medium would be unnecessary, besides optimizing and making less expensive the purification process. This work aims to evaluate the technical viability by utilizy electrodialysis (ED) technique as an alternative to separate lactobionic acid, from solutions containing lactose, fructose, and sorbitol, produced by biotechnological processes catalyzed by GFOR and GL of Z. mobilis. Ionics® membranes were used in this study, with AR204-SZRA specification for anion exchange membrane and CR67-HMP specification for cation exchange membrane, with 11cm² of permeating area for each one. Experiments were performed in a three-compartment ED stack with 120mL of volume each. Intermediate compartment received feed solution or bioconversion medium containing lactobionic acid, whilst anodic and cathodic compartments contained a sodium chloride solution (20gL-1). Electrolytes passage through the membrane was indirectly observed by measuring conductivity in the intermediate compartment. Lactobionic acid concentration, as well as concentration of other substances present in bioconversion medium, was determined by high performance liquid chromatography (HPLC). When using a constant current density, the applied voltage presented variation along the time. Thus, in order to avoid excessive increase of voltage and consequently an increase of electrical resistance of the system - that would result in concentration polarization - it was chosen to operate the system with a constant voltage. The best condition for the system was determined combining different voltages (5, 15, 30 ad 60V) with different lactobionic acid concentrations (1, 5, 10, 20 and 30gL-1). From lactobionic acid recovery results, maximum conductivity decreasing velocity, and apparent resistance of the system, the best voltage for the system operation was determined as 15V. Under this condition, crystallized lactobionic acid (ALC) recovery from a 20gL-1 standard solution was 38.7% in a 250min experiment. When compared to a standard solution containing all bioconversion components (lactose, fructose and sorbitol) the recovery was affected due to the presence of non-ionic substances, thus ALC recovery efficiency decreased to 16.2%. The same behavior was observed when the test was performed using a real diluted bioconversion medium, previously treated by micro-filtration for removal of impurities. Under these conditions, recovery was 14%. Despite relatively low efficiency due to the limitations of ED system used, the results of lactobionic acid permeation can be considered satisfactory. Higher recovery efficiencies could be obtained by increasing permeating area, either increasing membrane area or increasing the number of compartments in electrodialysis stack. The results suggest that lactobionic acid recovery using electrodialysis simultaneously to the biotechnological process of production can be feasible, since the costs involved with the application of this technique are justified by the added value of the product.
As enzimas glicose-frutose oxidorredutase (GFOR) e glicono-d-lactonase (GL), presentes em células da bactéria Zymomonas mobilis, têm a capacidade de catalisar a formação de ácido lactobiônico (AL), ou seus sais, e sorbitol utilizando lactose e frutose como substratos. O AL e o lactobionato de sódio têm importantes aplicações na área médica e na indústria de cosméticos. As enzimas GFOR e GL apresentam suas maiores atividades em pH 6,4, por esta razão, durante a produção do AL há a necessidade de corrigir o pH do meio a fim de mantê-lo em torno deste valor. A separação do ácido lactobiônico por eletrodiálise é possível, uma vez que esta substância é o único componente iônico da bioconversão. O processo de remoção do AL durante o processo de formação pode ser vantajoso, pois tornaria desnecessária a adição de base ao meio reacional, além de otimizar e desonerar o processo de purificação. Este trabalho teve como objetivo avaliar a viabilidade da utilização da técnica de eletrodiálise (ED) como alternativa para separação do ácido lactobiônico de soluções contendo lactose, frutose e sorbitol, provenientes de processo biotecnológico catalisado pela enzimas GFOR e GL de Z. mobilis. Foram utilizadas membranas Ionicsâ aniônica AR204-SZRA e catiônica CR67-HMP com 11cm² de área permeante. Os ensaios foram realizados em um sistema de ED de três compartimentos de 120mL de volume cada. No compartimento intermediário foi alimentada a solução ou o meio de bioconversão contendo o ácido lactobiônico, enquanto os compartimentos anódico e catódico continham solução de NaCl (20g.L-1). A passagem dos eletrólitos através das membranas foi acompanhada indiretamente pela medida da condutividade elétrica e, também, pela concentração de AL e das demais substâncias presentes no meio de bioconversão, as quais foram determinadas por cromatografia em fase líquida (HPLC). Com densidade de corrente elétrica constante, a diferença de potencial (ddp) elétrica aplicada variava ao longo do tempo. Deste modo, a fim de evitar um aumento excessivo da ddp e um conseqüente aumento na resistência elétrica do sistema, que poderia ocasionar uma polarização por concentração, optou-se por operar o sistema com diferença de potencial constante. A melhor condição foi determinada pela variação da ddp (5, 15, 30 e 60V) ao longo do tempo, para diferentes concentrações de ácido lactobiônico (1, 5, 10, 20 e 30g.L-1). A partir dos resultados percentuais de recuperação de AL, da velocidade máxima de redução da condutividade e da resistência aparente do sistema, a melhor ddp para operação do sistema de ED foi determinada em 15V. Nesta condição, a recuperação de ácido lactobiônico cristalizado com solvente orgânico (ALC), utilizado como padrão, presente na concentração de 20g.L-1, foi de 38,7% em 250min de ensaio. Quando comparada a uma solução padrão contendo todos os componentes presentes na bioconversão (lactose, frutose e sorbitol) a recuperação foi afetada pela presença das substâncias não iônicas e a eficiência de recuperação de ALC decresceu para 16,2%. O mesmo comportamento foi observado quando o teste foi realizado com um meio de bioconversão real diluído e previamente submetido a tratamento de microfiltração para remoção de impurezas, em que a recuperação foi de 14%. Apesar da eficiência relativamente baixa, em razão das limitações do sistema de ED utilizado, os resultados na permeação do ácido lactobiônico podem ser considerados satisfatórios. Maiores eficiências de recuperação poderiam ser obtidas com o aumento da área permeante, seja aumentando a área de membrana ou o número de compartimentos do sistema de eletrodiálise. Os resultados sugerem que a recuperação de ácido lactobiônico por eletrodiálise, simultaneamente ao processo biotecnológico de produção, pode ser viável uma vez que o custo envolvido com a aplicação desta técnica é justificado pelo alto valor agregado do produto.
Keywords: Bioquímica; Eletrodiálise; Ácido lactobiônico; Enzimas; Processo biotecnológico